2016
DOI: 10.1193/122813eqs298mr2
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Influence of Ground Motion Duration on Structural Collapse Capacity Using Spectrally Equivalent Records

Abstract: This study examines the influence of ground motion duration on the collapse capacities of a modern, five-story steel moment frame and a reinforced concrete bridge pier. The effect of duration is isolated from the effects of ground motion amplitude and response spectral shape by assembling sets of "spectrally equivalent", long and short duration records, and employing them in comparative non-linear dynamic analyses. For the modern steel moment frame, the estimated median collapse capacity is 29% lower when usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
241
3
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 256 publications
(270 citation statements)
references
References 38 publications
19
241
3
7
Order By: Relevance
“…Chandramohan et al found that, compared with other measures, significant duration ( D s ) was the most suitable IM for ground‐motion duration. Significant duration is defined as the time between two target values of the integral, truetrue∫0tmaxagt2dt, where a g is the ground acceleration, and t max is the total duration of the record.…”
Section: Existing Ims For Duration and Spectral Shapementioning
confidence: 99%
“…Chandramohan et al found that, compared with other measures, significant duration ( D s ) was the most suitable IM for ground‐motion duration. Significant duration is defined as the time between two target values of the integral, truetrue∫0tmaxagt2dt, where a g is the ground acceleration, and t max is the total duration of the record.…”
Section: Existing Ims For Duration and Spectral Shapementioning
confidence: 99%
“…Because of the increase in available ground motion data from recent subduction zone earthquakes, mainly from Japan and Chile, ground motion records from large subduction zone megathrust earthquakes can now be used . To isolate the effects of ground motion duration, Foschaar et al , and Chandramohan et al , , for example, selected ground motions with similar spectral shape and studied the relationship between the response and different intensity measures of ground motion duration.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic deterioration of the structural component is implicitly considered via a lumped-plasticity model for a single bridge pier using the Ibarra et al (2005) model. It should be noted that prior to Chandramohan et al (2015), none of the earlier numerical studies accounted for the effect of cyclic deterioration in the nonlinear structural models (Sarieddine and Lin 2013, Cornell 1997, Hancock and Bommer 2007, Iervolino et al 2006, and Raghunandan and Liel 2013. However, the Ibarra et al (2005) model that is employed in the Chandramohan et al (2015) study, does not account for cross section geometry and axial force-bending moment interaction of RC sections and components.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted by Chandramohan et al (2015), proposes a methodology to quantify the effect of ground-motion duration on the probability of structural collapse. In order to isolate the effect of duration from other ground-motion characteristics, such as amplitude and frequency content, they used spectrally equivalent, long and short duration record sets, with unmodified spectral content.…”
Section: Introductionmentioning
confidence: 99%